Metabolic Responses of Two Contrasting Sorghums to Water‐Deficit Stress. Issue 1 (1st January 2015) - Burke, John J.; Payton, Paxton; Chen, Junping; Xin, Zhanguo; Burow, Gloria; Hayes, Chad
ABSTRACT: Water‐deficit stress responses in sorghum [ Sorghum bicolor (L.) Moench] have been described in the literature as preflowering drought tolerant (postflowering senescent) or postflowering drought tolerant (preflowering drought sensitive). The underlying physiological mechanisms associated with these drought traits remain unclear. It was hypothesized that the preflowering drought sensitivity of stay‐green lines could be related to reported differences in osmotic potential among stay‐green and senescent lines resulting in an inability of the cultivars to either sense or respond the soil drying until the rate of drying is too great for the stay‐green lines to compensate. The objective of this study was to measure stress‐induced changes in relative water content, abscisic acid (ABA), proline, dhurrin, sucrose, and carbon assimilation during the onset of water‐deficit stress in the preflowering drought‐tolerant line SC1211–11E and the postflowering drought‐tolerant line BTx642 to determine if there were differential responses to the onset of soil drying. In both greenhouse and field studies, it was found that SC1211–11E had lower relative water contents and accumulated higher levels of ABA and proline than the BTx642. The SC1211–11E also showed increases in carbon assimilation shortly after the cessation of irrigation that declined with prolonged stress. These results provide new insights into the differential responses of pre and postflowering drought‐tolerant sorghum lines.